THE POTENTIAL OF THE MUNICIPALITY OF TRSTENIK FOR THE DEVELOPMENT OF THE WINE TOURISM - Milićević, Snežana; Stojković, Jelena (Economic Outlook, 2024)
The Trstenik vineyard is located on the Zupa wine road and possesses many wineries which are open for visitors, many hectares of vineyards, two wine festivals and many culturally historical monuments in its immediate surroundings. The purpose of the research is to inquire into the opinions of tourists regarding the possibilities for the development of wine tourism in the Trstenik vineyard, with the hopes of intensifying the tourism development of this municipality. The survey method was used to collect the primary data in the research. The survey was carried out during the months of April and May, 2024. There were 163 participants in the survey. The results have shown that the municipality of Trstenik possesses the potentials for wine tourism development, but that they are not being adequately utilized. Namely, tourists come to Trstenik, but not for the wine and wine tourism. The results of the research are significant as they can assist tourism organization as well as municipal officials to make up a strategy for the development of wine tourism which would secure a significant position on the Serbian wine tourism map for the Trstenik wine district.
Keywords: Wine tourism; Trstenik; Trstenik wine district; tourist destination